Eliminating hepatitis C in Australia: a novel model of hepatitis C testing and treatment for people who inject drugs at a medically supervised injecting facility. Issue 6 (14th March 2023) - MacIsaac, Michael B; Whitton, Bradley; Hubble, Adrian; Cogger, Shelley; Penn, Matthew; Weeks, Anthony; Elmore, Kasey; Pemberton, David; Anderson, Jenine; Howard, Rebecca; McKeever, Una; Papaluca, Timothy; et al.
Abstract: Objective: To evaluate the feasibility of testing and treating people who inject drugs at a supervised injecting facility for hepatitis C virus (HCV) infection. Design: Retrospective cohort study. Setting, participants: People who inject drugs who attended the Melbourne supervised injecting facility, 30 June 2018 – 30 June 2020. Main outcome measures: Proportion of people tested for hepatitis C; proportions of people positive for anti‐HCV antibody and HCV RNA, and of eligible people prescribed direct‐acting antiviral (DAA) treatment; sustained virological response twelve weeks or more after treatment completion. Results: Of 4649 people who attended the supervised injecting facility during 2018–20, 321 were tested for hepatitis C (7%); 279 were anti‐HCV antibody‐positive (87%), of whom 143 (51%) were also HCV RNA‐positive. Sixty‐four of 321 had previously been treated for hepatitis C (20%), 21 had clinically identified cirrhosis (7%), eight had hepatitis B infections (2%), and four had human immunodeficiency virus infections (1%). In multivariate analyses, people tested for hepatitis C were more likely than untested clients to report psychiatric illness (adjusted odds ratio [aOR], 9.65; 95% confidence interval [CI], 7.26–12.8), not have a fixed address (aOR, 1.59; 95% CI, 1.18–2.14), and to report significant alcohol use (aOR, 1.57; 95% CI, 1.06–2.32). The median number of injecting facility visits was larger for those tested for hepatitis C (101; interquartile range [IQR], 31–236) than for those not tested (20; IQR, 3–90). DAA treatment was prescribed for 126 of 143 HCV RNA‐positive clients (88%); 41 of 54 with complete follow‐up data were cured (76%). Conclusions: People who attend supervised injecting facilities can be tested and treated for hepatitis C on site. Models that provide streamlined, convenient hepatitis C care promote engagement with treatment in a group in which the prevalence of hepatitis C is high.